KEY ASPECTS OF RESEARCH OF PRIORITY VALUE OF INNOVATIVE ACTIVITY AS AN OBJECT OF STATE REGULATION IN MODERN ECONOMY - Elena Manchuk (Вестник Северо-Кавказского федерального университета, 2022)
The scientific article under consideration is very actual nowadays. The matter is in today's economy, innovation development should be due to the increased efficiency of the economic activity of any enterprise. Innovation activity in the early stages requires substantial investment. In this article, based on the study of the basic principles, role of the state, the significance of a system approach evaluating the economic efficiency of innovation activities of small businesses is determined. It is the efficiency of economic assessments of innovation and investment activities of small enterprises that signifies and defines their effectiveness.